The readiness of youngster to be global via online entrepreneurship / Naqib Akmal Sholikhin - Sholikhin, Naqib Akmal (Faculty of Business and Management, 2018)
Entrepreneurship is the willingness to engage into entrepreneurial behavior in the future. Entrepreneurship intention may be affected by different factors. The purpose of this study is to investigate the factors that may influence to the readiness of youngster to be global via online entrepreneurship. The population for this study is 174,900 of young adult in Melaka and the researcher use purposive sampling method to be used as the respondent.The target respondent for this study among young adult which the age is between 18 to 35 years old. The Questionnaire were given to 179 young adult. Out of 179, only 175 were returned and 4 has not been accepted. After the collection of data, a code was developed for each variable before being transferred to the computer for analysis. In this study, the researcher will use the Statistical Package for Social Sciences (SPSS) as the study statistics software to analyze data that has been collected. To be added, few statistical tools will be used in this study such as Reliability Analysis, Frequency Analysis, Descriptive Analysis and Multiple Regressions.